2021
DOI: 10.3390/genes12050696
|View full text |Cite
|
Sign up to set email alerts
|

Sp1-Mediated circRNA circHipk2 Regulates Myogenesis by Targeting Ribosomal Protein Rpl7

Abstract: Circular RNAs (circRNAs) represent a class of covalently closed single-stranded RNA molecules that are emerging as essential regulators of various biological processes. The circRNA circHipk2 originates from exon 2 of the Hipk2 gene in mice and was reported to be involved in acute promyelocytic leukemia and myocardial injury. However, the functions and mechanisms of circHipk2 in myogenesis are largely unknown. Here, to deepen our knowledge about the role of circHipk2, we studied the expression and function of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…For example, it has been shown that transcription factor YY1 can bind to the promoter of circ-ZNF609 and regulate the progression in cholangiocarcinoma ( 47 ). The promoter of circHipk2 has also been found to be regulated by transcription factor Sp1 and circHipk2 is regarded as an important candidate regulating myogenesis ( 48 ). The transcriptional activity of circITGB1 derives from the main promoter region upstream of ITGB1 coding sequence, which includes several transcription factor binding sites ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that transcription factor YY1 can bind to the promoter of circ-ZNF609 and regulate the progression in cholangiocarcinoma ( 47 ). The promoter of circHipk2 has also been found to be regulated by transcription factor Sp1 and circHipk2 is regarded as an important candidate regulating myogenesis ( 48 ). The transcriptional activity of circITGB1 derives from the main promoter region upstream of ITGB1 coding sequence, which includes several transcription factor binding sites ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, circRNA ARF1 expression in glioma stem cells is regulated by U2AF2 [33]. circRNA circHipk2 expression in C2C12 myoblasts is mediated by Sp1 [34], and circ-FOXP1 in hepatocellular carcinoma cells is regulated by SOX9 [9][10][11]. Therefore, we investigated the upstream regulator of circGFRA1 in PCa cells showing that circGFRA1 is regulated by LMX1B, which has previously been shown to be involved in many cancers, including ovarian, esophageal, and glioma [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…DNA 5-methylcytosine (5mC) and RNA N6-methyladenosine (m 6 A) are two typical epigenetic modifications that play essential roles in transcription and post-transcription regulation, respectively [ 9 11 ]. Recently, many studies have explored the epigenetic mechanisms underlying skeletal muscle growth and development in mammals, including chromatin landscape [ 12 , 13 ], microRNA [ 14 , 15 ], circRNA [ 16 , 17 ], DNA and histone modifications [ 14 , 18 ]. The discovery of the RNA methylation system in post-transcriptional regulation of myoblast differentiation and proliferation provides another layer of information for understanding skeletal muscle development and growth [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%